2021
DOI: 10.1287/mnsc.2020.3679
|View full text |Cite
|
Sign up to set email alerts
|

Can Brands Claim Ignorance? Unauthorized Subcontracting in Apparel Supply Chains

Abstract: Unauthorized subcontracting—when suppliers outsource part of their production to a third party without the retailer’s consent—has been common practice in the apparel industry and is often tied to noncompliant working conditions. Because retailers are unaware of the third party, the production process becomes obscure and cannot be tracked. In this paper, we present an empirical study of the factors that can lead suppliers to engage in unauthorized subcontracting. We use data provided by a global supply chain ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 36 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…For example, some studies have focused supply chain analysis toward vertical multi-tier supply chain management (e.g. Tachizawa and Wong, 2014;Carter et al, 2015;Meinlschmidt et al, 2018;Villena, 2019), thereby neglecting potentially vast horizontal complexities that may arise on single supply chain tiers through the practice of (unauthorized) subcontracting (Caro et al, 2020;Gold et al, 2020). The study in this issue by Nath et al (2020) shows an example of how unanticipated consequences can be identified by horizontally examining subsupplier relations.…”
Section: A Model Of the Antecedents Of (Un)anticipated Consequences In Sustainable Oscmmentioning
confidence: 99%
“…For example, some studies have focused supply chain analysis toward vertical multi-tier supply chain management (e.g. Tachizawa and Wong, 2014;Carter et al, 2015;Meinlschmidt et al, 2018;Villena, 2019), thereby neglecting potentially vast horizontal complexities that may arise on single supply chain tiers through the practice of (unauthorized) subcontracting (Caro et al, 2020;Gold et al, 2020). The study in this issue by Nath et al (2020) shows an example of how unanticipated consequences can be identified by horizontally examining subsupplier relations.…”
Section: A Model Of the Antecedents Of (Un)anticipated Consequences In Sustainable Oscmmentioning
confidence: 99%
“…In this way, a supply network was simulated based on subcontracting, as described by Labowitz and Baumann‐Pauly (2014) as well as Caro et al. (2019).…”
Section: Diffusion Modelmentioning
confidence: 99%
“…Later on, the question of how sustainability spreads along supply chains and networks gained academic attention (e.g., Marshall, McCarthy, Claudy, & McGrath, 2019), although studies on the diffusion of sustainability along multiple tiers of supply chains remain scant. Even more limited is research that covers the phenomenon of subcontracting in supply networks (Caro, Lane, & Saez de Tejada Cuenca, 2019; LeBaron, 2018). This is astonishing since subcontracting represents a highly relevant phenomenon in the goal of sustainability in supply networks; such practice may substantially enhance complexity and blur the visible horizon of focal companies (Carter et al., 2015) even if only a few supply chain tiers are involved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations